Capacity Development: Making Village Regulations Concerning the Protection of Migrant Workers in Arjowilangun Village, Kalipare District, Malang Regency - Setijaningrum, Erna; Wahyuni Triana, Rochyati; Dwi Arifriyanti, Riana; Qurota Mawa Adna, Anisa (Journal of Governance and Administrative Reform, 2023)
Arjowilangun Village is situated in the Kalipare District of the Malang Regency and is a major contributor of migrant workers. In reality, the large number of workers who go abroad causes a wide range of problems, including failed departures, illness while working abroad, layoffs before the end of contracts, deceptive contracts, deportation, visa overstaying, nonpayment, and victimization by crime. In this, there is a growing need to protect the villagers of Arjowilangun through regulatory and other legal means. In numerous unfortunate occurrences, the capacity of many manpower is insufficient to comply with Village Regulations. Our Universitas Airlangga Team of Community Service has conducted training and mentoring as part of our collective effort to enhance the organizational capacity for addressing the needs of the community. Particularly, the UNDP's Capacity Development frameworks guided our community service, including engaging stakeholders on capacity development, assessing capacity assets and needs, developing a capacity development response, putting that response into action, and evaluating capacity development. Our service was attended by 37 individuals, including village officials, members of the village representative body, former migrant workers, migrant workers' families, and community leaders. The community service reveals that the knowledge gained as a result of the capacity building efforts was substantial, allowing village leaders in Arjowilangung and other diverse parties to draft local regulations to protect migrant workers. The service and dedication of those involved in both the mentoring and training programs have a significant impact on this, with the support and additional motivation of the village apparatus ensuring that migrant workers receive the best possible services and safety.